Optimisation of 3% Giemsa Staining Time in Malaria Microscopic Examination - Resa Cristina Lilik Hadiana; Adhi Kumoro Setya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Malaria infection is a significant health issue in Indonesia, with a high prevalence in endemic areas such as Puskesmas Hanura Teluk Pandan. Giemsa 3% staining is used as the standard method for microscopic diagnosis of malaria; however, the duration of staining can affect laboratory efficiency. This study aims to optimize the staining time of Giemsa 3% in microscopic malaria diagnosis to improve efficiency without compromising diagnostic quality. The study used an experimental design with staining time variations of 30 minutes, 40 minutes, and 50 minutes on thin blood smear samples from suspected malaria patients. Staining quality was assessed using a scoring system, with a score of 1 indicating optimal staining (clear background, blue cytoplasm, and red nucleus) and a score of 0 indicating suboptimal staining (unclear background, cytoplasm, and nucleus not stained or not clearly visible). The results showed that all staining time variations produced optimal staining quality (score 1), with no samples receiving a score of 0. The data were found to be non-homogeneous and non-normally distributed, thus the Kruskal-Wallis test was employed for subsequent analysis. The Kruskal-Wallis test showed no significant differences between the three staining time variations (p = 1.000). The conclusion of this study is that staining durations of 30 minutes, 40 minutes, and 50 minutes with Giemsa 3% can produce equivalent staining quality, allowing operational efficiency without compromising the accuracy of malaria diagnosis.